Influence of Cultural Norms on Gender Representation in Media in Kenya - Kiarie, Alex (Journal of Communication, 2025)
Purpose: The purpose of this article was to analyze influence of cultural norms on gender representation in media in Kenya. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: In Kenya, cultural norms influence media portrayals, with women often shown in domestic roles and men in positions of authority. While some media, like True Love East Africa, are shifting towards more equitable representations, traditional gender stereotypes persist, indicating ongoing cultural influence. Unique Contribution to Theory, Practice and Policy: Social cognitive theory (SCT), cultivation theory & feminist media theory may be used to anchor future studies on the influence of cultural norms on gender representation in media in Kenya. Media producers, content creators, and filmmakers should actively incorporate diverse and empowered gender representations into their content. Governments and regulatory bodies should implement policies that encourage balanced gender representation in the media. These policies can include incentives for media companies that create content with equal gender representation in leadership, professional, and domestic roles.